2000
DOI: 10.1007/s000110050597
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the effect and mechanisms of action of nicotine in inflammatory bowel disease

Abstract: Nicotine reduced inflammation in the TNBS model of colonic damage confirming the use of nicotine in IBD although the choice of dose requires further investigation. The mechanism of action of nicotine does not involve increased corticosterone levels, but may be a consequence of a reduction in TNFalpha or leukotriene B4 production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 24 publications
5
35
0
Order By: Relevance
“…Exacerbation of the DAI score at high doses of nicotine was not observed in s.c. or minipump nicotine-treated animals, suggesting a differential effect of nicotine dose and delivery on colonic inflammation. The results suggesting the protective effects of low-dose nicotine added to the drinking water were similar to those reported in various experimental colitis models in rats and mice (Qiu et al, 1997;Eliakim et al, 1998;Sykes et al, 2000;Ghia et al, 2006). Qiu et al (1997) demonstrated that a 5-mg/ml dose of nicotine in the drinking water in 2,4-dinitrobenzene sulfonic acid (DNBS)-treated rats resulted in a significant decrease in intestinal inflammation; however, the inflammation was shown to increase at a dose of 50 mg/ml.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Exacerbation of the DAI score at high doses of nicotine was not observed in s.c. or minipump nicotine-treated animals, suggesting a differential effect of nicotine dose and delivery on colonic inflammation. The results suggesting the protective effects of low-dose nicotine added to the drinking water were similar to those reported in various experimental colitis models in rats and mice (Qiu et al, 1997;Eliakim et al, 1998;Sykes et al, 2000;Ghia et al, 2006). Qiu et al (1997) demonstrated that a 5-mg/ml dose of nicotine in the drinking water in 2,4-dinitrobenzene sulfonic acid (DNBS)-treated rats resulted in a significant decrease in intestinal inflammation; however, the inflammation was shown to increase at a dose of 50 mg/ml.…”
Section: Discussionsupporting
confidence: 85%
“…Qiu et al (1997) demonstrated that a 5-mg/ml dose of nicotine in the drinking water in 2,4-dinitrobenzene sulfonic acid (DNBS)-treated rats resulted in a significant decrease in intestinal inflammation; however, the inflammation was shown to increase at a dose of 50 mg/ml. Similarly, Eliakim et al (1998) and Sykes et al (2000) reported that nicotine had a dual effect on colitis in mice, with low doses of nicotine being more effective at reducing the inflammation than higher doses. This dual anti-inflammatory effect of nicotine in the form of an "inverted-U" was described previously (Picciotto, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…Nicotine suppresses inflammation during experimental ulcerative colitis (22), improves survival during experimental sepsis via its effect on the production of proinflammatory mediators (23), and blocks leukocyte recruitment in vivo (24). Nicotine suppresses TNF production by LPS-stimulated macrophages (25) and microglial cells (26) through the alpha7 nicotinic acetylcholine receptor (α7nAChR), and inhibits endothelial cell activation in vitro and in vivo (24).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a preliminary study suggests that DSS-induced colitis is more severe in mice deficient in nicotinic receptors (28). Although part of the beneficial effect of nicotine is presumably due to its immunosuppressive properties (41,47), cholinergic events that are tilted in favor of absorption, rather than secretion, would be expected to alleviate some of the diarrhea experienced by patients with ulcerative colitis. The present study was designed to further define the mechanism of altered ion transport in the colon of mice with DSS-induced colitis and has revealed a novel pathway involving nicotinic-nitrigeric communication and, possibly, participation by enteric glial cells in the cholinergic control of ion transport.…”
mentioning
confidence: 99%